Respuesta :
The slope-intercept form is:
y = mx + b
where m = slope, and b = y-intercept.
You need a slope of 1, so m = 1.
You need a y-intercept of -1, so b = -1.
Replace m with 1 and b with -1 in the slope intercept form to get
y = 1x + (-1)
which simplifies to
y = x - 1
y = mx + b
where m = slope, and b = y-intercept.
You need a slope of 1, so m = 1.
You need a y-intercept of -1, so b = -1.
Replace m with 1 and b with -1 in the slope intercept form to get
y = 1x + (-1)
which simplifies to
y = x - 1